2019
DOI: 10.1080/13669877.2019.1628096
|View full text |Cite
|
Sign up to set email alerts
|

Collective efficacy and natural hazards: differing roles of social cohesion and task-specific efficacy in shaping risk and coping beliefs

Abstract: Previous research in non-disaster contexts has shown that the concept of collective efficacy, which is a group's sense of its ability to achieve a specific objective, assists understanding of community readiness and households' decisions to take preparedness actions. Collective efficacy expands the concept of social capital, which refers to social resources such as trust, norms and networks, by addressing how likely communities are to activate these resources for specific tasks. This paper empirically investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 67 publications
2
41
0
Order By: Relevance
“…Although some studies indicated that self-efficacy exerted more influence on planning for preparedness than actual preparedness behaviors [ 64 ], this analysis followed the same observations from Mumbai, Taiwan, and Australia [ 29 , 34 , 65 ]. Besides, we are aware that scholars have proposed several types of efficacies recently, such as the collective efficacy (how community or government can handle the potential disasters effectively) [ 31 , 32 ] or the responsive/outcome efficacy (how effective the actions adopted in disaster risk reduction are in reducing the impact from potential disasters) [ 28 , 29 , 30 ]. This paper contributes to our understanding that self-efficacy can directly promote disaster preparedness and play a mediation role between other variables, such as place attachment in this study and the disaster preparedness behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies indicated that self-efficacy exerted more influence on planning for preparedness than actual preparedness behaviors [ 64 ], this analysis followed the same observations from Mumbai, Taiwan, and Australia [ 29 , 34 , 65 ]. Besides, we are aware that scholars have proposed several types of efficacies recently, such as the collective efficacy (how community or government can handle the potential disasters effectively) [ 31 , 32 ] or the responsive/outcome efficacy (how effective the actions adopted in disaster risk reduction are in reducing the impact from potential disasters) [ 28 , 29 , 30 ]. This paper contributes to our understanding that self-efficacy can directly promote disaster preparedness and play a mediation role between other variables, such as place attachment in this study and the disaster preparedness behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, this analysis only employed data from a province with relatively fewer occurrences of disasters in China, and thus the overall generalization of this study might be needed. Thirdly, we only included limited dimensions of place attachment and efficacy measures in this analysis; studies including other dimensions of place attachment or types of efficacies such as the collective efficacy and response efficacy [ 28 , 29 , 30 , 31 , 32 ] are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent study by Babcicky and Seebauer [18], collective efficacy or a group's shared belief in its joint capabilities to achieve an objective, influences risk perception, anxiety, and self-efficacy towards protective action. These studies [17], [18] indicate a complex interrelatedness between the beliefs that buttress self-efficacy and collective efficacy.…”
Section: Factors Affecting Self-help Mutual Assistance and Disaster mentioning
confidence: 99%
“…In literature on collective action, efficacy is oftentimes associated with and predicted by group identification (Drury and Reicher, 2005 , 2009 ; Van Zomeren et al, 2008 ; Blackwood and Louis, 2012 ; Greenaway et al, 2015 ; Vestergren et al, 2016 ). Likewise, social support was frequently mentioned in qualitative interviews as a prerequisite for collective efficacy (Drury and Reicher, 1999 ; see also Babcicky and Seebauer, 2020 ). Other authors have underlined the following group cohesion characteristics as possible efficacy predictors: appreciation and encouragement from others (Drury and Reicher, 1999 ; Almers, 2013 ), reciprocity (Lubell et al, 2007 ; Collins et al, 2014 ), trust (Collins et al, 2014 ), and social norms (Van Zomeren et al, 2004 ; Doherty and Webler, 2016 ; Wang and Lin, 2017 ).…”
Section: Introductionmentioning
confidence: 99%